2012
DOI: 10.1002/pchj.4
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, emotional contagion, and rapid facial reactions to angry and happy facial expressions

Abstract: The aim was to explore whether emotional empathy is related to the capacity to react with rapid facial reactions to facial expressions of emotion, and if emotional empathy is related to the ability to experience a similar emotion as expressed by another person. People high or low in emotional empathy were exposed to pictures of happy and angry faces while their facial electromyography from the zygomaticus major and corrugator supercilii muscle regions was detected. High empathy participants rapidly reacted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 74 publications
(110 reference statements)
3
63
0
7
Order By: Relevance
“…One measure that has more commonly been employed to study sex differences in empathy is facial electromyographic (EMG), which measures facial mimicry, and is positively associated with empathy (Dimberg et al, 2011; Dimberg and Thunberg, 2012) and facial expression recognition (e.g., Sato et al, 2013). Indeed, a number of studies report greater facial muscle reactivity in females, compared to males, when exposed to facial expressions (Dimberg and Lundquist, 1990; Lundqvist, 1995).…”
Section: Neuronal Mechanisms For Empathymentioning
confidence: 99%
“…One measure that has more commonly been employed to study sex differences in empathy is facial electromyographic (EMG), which measures facial mimicry, and is positively associated with empathy (Dimberg et al, 2011; Dimberg and Thunberg, 2012) and facial expression recognition (e.g., Sato et al, 2013). Indeed, a number of studies report greater facial muscle reactivity in females, compared to males, when exposed to facial expressions (Dimberg and Lundquist, 1990; Lundqvist, 1995).…”
Section: Neuronal Mechanisms For Empathymentioning
confidence: 99%
“…Consistent with trait activation theory (Tett & Burnett, ), prior research has found that the extent to which empathy‐relevant situations are associated with empathic reactions to those situations depends on the observer's level of trait empathy. For example, research has found that exposing participants to photos of happy and angry faces produces congruent facial expressions in subjects with high trait affective empathy but not low trait affective empathy (Dimberg & Thunberg, ; see also Sonnby–Borgström, ; Westbury & Neumann, ). These findings underscore the need for a multilevel approach when examining how and under what conditions empathy can be changed and are consistent with recent theory outlining how trait empathy may interact with state empathy when predicting outcomes (Cropanzano et al, ).…”
Section: Critical Review Of Empathy Research In Organizational Behaviormentioning
confidence: 99%
“…The emphasis of AE is representatively focused on experiencing the emotional states of others consciously, which implies a self-other distinction (Eres et al, 2015;Mattan et al, 2016), as well as an understanding of the origin of emotional experience (Bernhardt & Singer, 2012). AE differs from emotion contagion, which responds automatically to another person's emotional state but not necessarily self-other distinction (de Waal, 2012;Dimberg & Thunberg, 2012;Mattan et al, 2016). Emotion contagion may depend on brain regions that are activated in correlation with recognition of others' emotions through facial expression and prosody (Leigh et al, 2013).…”
Section: Evaluation Of Aementioning
confidence: 99%